CEE trade in services: Value added versus gross terms approaches - Aleksandra Kordalska; Magdalena Olczyk (Gdańsk University of Technology, Faculty of Management and Economics, 2018)
This paper aims to assess the impact of determinants on service exports in both value added terms and in gross terms for seven Central Eastern European economies in years 1995-2011. The results confirm the importance of increasing labour productivity and highly-skilled and medium-skilled workers for growth in services trade. Exports of services are also supported by linkages between domestic services, especially business services, and the manufacturing sector. The results show the impacts of the determinants are fairly similar when exports are measured in value added terms or in gross terms, however the strength of impact differs in some subgroup of analysed countries.
Keywords: C23; D54; F14; L80; 330; gross exports; value added exports; CEE economies; trade in services